Penerapan Konsep Education for Sustainable Development (ESD) dalam Pengembangan Soal Literasi dan Numerasi untuk Mempersiapkan Generasi Emas 2045 - Siregar, Adzkia Rizkianisa Awira; Adna, Ayla Zahra; Daulay, Intan Maharani; Lubis, M. Joharis (Majalah Ilmiah METHODA, 2025)
Education plays a crucial role in developing the Golden Generation 2045 who excel in literacy and numeracy. Unfortunately, PISA 2018 revealed that Indonesian students' literacy and numeracy skills are still below the OECD countries' average. Education for Sustainable Development (ESD) presents a new approach in developing evaluation instruments that not only assess academic abilities but also build sustainable awareness. This research used a qualitative descriptive method, with data collection techniques including observation, in-depth interviews, and documentation. The data was analyzed using data reduction techniques, data presentation, and conclusion drawing. This article explores the application of ESD concepts in developing literacy and numeracy questions and the obstacles faced by educators. The results of this study indicate that most teachers still have difficulty developing HOTS (Higher Order Thinking Skills) questions with stimuli related to ESD. Therefore, training programs and strategic approaches are needed to help teachers create more contextual questions and encourage students' critical thinking skills.